Health Tourism Product User Profile - Yanakieva, Albena; Karadzhova, Zlatina (Research Papers, 2021)
A healthy lifestyle will always be up-to-date. Even in times of crisis, when it comes to one’s health and well-being, people do not stop caring for themselves. Nowadays, they are well educated and expect a return on investment. They want information that will improve their quality of life and real results.The purpose of this report is to establish, through a survey, the user profile of the health tourism product. The tasks set are: 1) to determine the specific therapeutic procedures to which the relevant contingent of tourists would be interested; 2) to specify the ways of assistance from the tour operators for the development of health tourism in the region of Burgas. Results, conclusions and recommendations for reaching the necessary competitive level of Burgas District are presented, as a recreation center for treatment and prevention.